Giving hope : conversations with children about illness, death, and loss - Lister, Elena; Schwartzman, Michael, 1953- (Avery, 2022)
"The best and only resource you will ever need for helping any child understand and cope with loss and death. Just as death is inevitable, talking about death is an inevitable part of parenting. Drs. Lister and Schwartzman offer us the way to have conversations that are as much about life as they are about death; conversations that anyone who parents, teaches, or counsels children can have. Giving Hope is a must-have resource that expands our understanding of how to prepare for, initiate, and facilitate these personal and profound conversations. The approach is honest, practical, and compassionate, and will benefit a grieving child now and in the future. Giving Hope gives us tools to make our children's experiences positive and life-affirming"--